Differences in immune responses to Haemonchus contortus infection in the susceptible Ile de France and the resistant Santa Ines sheep under different anthelmintic treatments regimens - Albuquerque, Ana Cláudia A. [UNESP]; Bassetto, Cesar Cristiano [UNESP]; Almeida, Fabiana A. [UNESP]; Hildersley, Katie A.; McNeilly, Tom N.; Britton, Collette; Amarante, Alessandro F. T. [UNESP] (Springer Nature, 2019)
Understanding the immunological basis of resistance to gastrointestinal nematode infections in livestock is important in order to develop novel methods of parasite control such as vaccination or genetic selection for parasite resistance. The present study aimed to investigate differences in immune response between parasite resistant Santa Ines and susceptible Ile de France sheep breeds to natural Haemonchus contortus infection. Parasitological parameters, humoral immunity, local and circulating cellular immune responses were evaluated in 19 Santa Ines and 19 Ile de France lambs undergoing different anthelmintic treatments regimens: suppressive treatments (SUP) or targeted selective treatments (TST) over a 5-month grazing period. Santa Ines lambs had significantly lower Haemonchus faecal egg count and worm burden compared to Ile de France regardless of treatment regime. In addition, circulating blood eosinophils count and parasite-specific IgG levels were significantly higher and more rapidly induced in Santa Ines lambs. Abomasal immune responses were generally greater in the resistant breed, which had significantly higher levels of parasite-specific IgA in mucus, and elevated number of globule leukocytes and CD3+ T cells within the abomasal mucosal. Furthermore, numbers of POU2F3+ epithelial cells, a tuft-cell specific transcription factor, were also elevated in the Santa Ines breed, suggesting that this breed is better able to initiate T-helper type 2 immune responses within the abomasum. In conclusion, the differential immunological responses detailed here are relevant to understanding resistance to gastrointestinal nematodes in other host breeds, as well as to resistance breeding as a sustainable control approach for parasitic infections.